الشخصية المعنوية للشركة خلال مرحلة التصفية في القانون اليمني و وفي ضوء الفقه الاسلامي - أحمد محمد الغشامي, حسين (revue mofakir, 2018)
This study handled the legal personality of the company during liquidation in accordance with Yemeni law and a comparative study with Islamic law. This study examines the provisions of Yemeni law regarding the Liquidation of Company and the extent to which its provisions are found to be in accordance with the principles of Islamic jurisprudence. The researcher analysed the context of the Yemeni company law paragraphs connected with the legal personality of the company during liquidation and used the inductive methodology, tracing all of the ideas and injunctions related to the issue of liquidation in the books of Islamic jurisprudence, in addition to other books and research. Then the researcher used comparative methodology to highlight the importance of the legal personality of the company during liquidation from both shariah and modern legal Perspective. Finally, the researcher suggests a number of recommendations which may contribute to the enactment of laws in a more accurate manner.